SCORCH: A Screenplay Exploring the Effects of Capitalism to the Working People and Environment in a Dystopian World - Nicole Naomi Hidajat; Stefanny Irawan (Institute of Research and Community Outreach - Petra Christian University, 2024)
The planet is currently facing a crisis, and capitalism plays a part in it as it affects both the workers and the provider, nature. This paper aims to show the effects of capitalism to the working people and environment in a dystopian world where nature is on the brink of destruction, using screenplay as the creative medium, and dystopian genre. This creative work uses the theories of ecological Marxism and class struggle. Annie, an epitome of the working people in Outside, has to endure the exhaustion as capitalism run by the ruler of Inside leads to long working hours and product alienation, malnutrition due to the lack of food and water, as well as anxiety as her sister falls sick. The intense capitalistic production leads to resource depletion in the form of drought as well as the scorching heat. To make things worse, the Outside people are being treated unjustly, causing mass action.